Comparative study on modular and traditional approaches in teaching mathematics in Agusan del Sur State College of Agriculture and Technology, Academic Year 2005-2006 - Misa, Virgel B.; Regahal, Irish May S.; Abangolan, Nilda G. (2007)
The researchers conducted this study to compare results of performance in Mathematics between the controlled group as representing traditional teaching and experimental group who adopted modular instruction in the First Year High School students of Agusan del Sur State College of Agriculture and Technology, Laboratory School, Academic Year 2006-2007. Data were gathered from the pretest and posttest results in both controlled and experimental groups were the variables used in this study. Based from the findings, the use of the modular approach in teaching mathematics had made significant improvement in the learners' achievement and confidence regardless of their abilities compared to traditional teaching. It could be inferred that the performance in higher mathematics largely depended on the learners' mathematical ability and understanding of basic mathematical concepts. The modular approach in teaching mathematics had positive effects on the respondents' achievement and confidence level most especially among the slow learners.
Keywords: Modular teaching; Mindanao studies; Teaching methods